2019
DOI: 10.1038/s41598-019-49159-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preservative-free 3% Diquafosol in Patients with Pre-existing Dry Eye Disease after Cataract Surgery: A Randomized Clinical Trial

Abstract: Dry eye disease (DED) after cataract surgery has become a critical concern, and various therapeutic options have been developed. Recently, preservative-free diquafosol ophthalmic solution has been introduced; however, its therapeutic effect on DED after cataract surgery has not been reported. We investigated the efficacy of preservative-free diquafosol in patients with pre-existing DED after cataract surgery. We divided subjects who were diagnosed with DED and scheduled to undergo cataract surgery, into 3 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…Similar findings showing the superiority of Diquafosal in the management of post-operative DED compared to artificial tears have been documented in other RCTs. 115 117 The results of a recent meta-analysis of these RCTS by Zhao et al. 118 suggested that topical diquafosal 3% is more effective than artificial tears in the post-operative management of DED.…”
Section: Considerations Of the Management Of Cataract Surgery Associamentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings showing the superiority of Diquafosal in the management of post-operative DED compared to artificial tears have been documented in other RCTs. 115 117 The results of a recent meta-analysis of these RCTS by Zhao et al. 118 suggested that topical diquafosal 3% is more effective than artificial tears in the post-operative management of DED.…”
Section: Considerations Of the Management Of Cataract Surgery Associamentioning
confidence: 99%
“…Similar findings showing the superiority of Diquafosal in the management of post-operative DED compared to artificial tears have been documented in other RCTs. [115][116][117] The results of a recent meta-analysis of these RCTS by Zhao et al 118 suggested that topical diquafosal 3% is more effective than artificial tears in the post-operative management of DED. At present this medication is not available in Europe but given its actions in reducing conjunctival goblet cell loss, which is known to occur after cataract surgery, 6,51 hopefully its introduction will help in the management of cataract surgery associated DED.…”
Section: Post-operative Management Of Dedmentioning
confidence: 99%
“…However, we hypothesize that preservative-free lubricants may be safer than eye drops with preservatives in patients with DED. [26][27][28] All AEs were resolved by the end of the study period and no safety issues were raised.…”
Section: Discussionmentioning
confidence: 96%
“…Park et al concluded that the postoperative use of 3% DQS could significantly improve TBUT, corneal fluorescein stain score, and conjunctival lissamine stain score as compared to HA 22 . Although some other studies have examined the effect of DQS on DES after cataract surgery 15 , 17 , 19 , 23 , the included subjects had already had DES. The present study recruited patients with no ocular surface diseases, including DES, and revealed that the treatment of healthy eyes with 3% DQS could also effectively improve TBUT after cataract operation.…”
Section: Discussionmentioning
confidence: 99%